2007
DOI: 10.1007/978-3-540-34891-7_19
|View full text |Cite
|
Sign up to set email alerts
|

The Mg2+ and Mg2+-Nucleotide-Regulated Channel-Kinase TRPM7

Abstract: TRPM7 is a member of the melastatin-related subfamily of TRP channels and represents a protein that contains both an ion channel and a kinase domain. The protein is ubiquitously expressed and represents the only ion channel known that is essential for cellular viability. TRPM7 is a divalent cation-selective ion channel that is permeable to Ca 2+ and Mg 2+ , but also conducts essential metals such as Zn 2+ , Mn 2+ , and Co 2+ , as well as nonphysiologic or toxic metals such as Ni 2+ , Cd 2+ , Ba 2+ , and Sr 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 45 publications
2
83
0
2
Order By: Relevance
“…Schweyen and colleagues (7,47,180) studied Mrs2 amino acid structure to determine the relationship of group II intron splicing with changes in Mrs2 transport, inasmuch as both functions are associated. Because Mrs2 shares some amino acid sequences with bacterial CorA, the availability of the crystal structure of CorA may be informative in describing Mg 2ϩ movement through the mammalian Mrs2 protein (87,105 (107,127,156). TRPM proteins possess six predicted TMs.…”
Section: Mammalian Mg 2؉ Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Schweyen and colleagues (7,47,180) studied Mrs2 amino acid structure to determine the relationship of group II intron splicing with changes in Mrs2 transport, inasmuch as both functions are associated. Because Mrs2 shares some amino acid sequences with bacterial CorA, the availability of the crystal structure of CorA may be informative in describing Mg 2ϩ movement through the mammalian Mrs2 protein (87,105 (107,127,156). TRPM proteins possess six predicted TMs.…”
Section: Mammalian Mg 2؉ Transportersmentioning
confidence: 99%
“…Hydrophobic regions between TM5 and TM6 are thought to contribute to the cation pore when four channel subunits coalesce to form the functional transporter (16). Unlike other members of the TRPM channel superfamily, the homologs TRPM6 and TRPM7 possess a COOH terminus, Thr/Ser kinase, that belongs to an atypical family of eukaryotic ␣-kinases (107,127). According, these proteins are termed "chanzymes."…”
Section: Mammalian Mg 2؉ Transportersmentioning
confidence: 99%
“…Other aspects of TRPM channels are addressed in a number of excellent review articles. 7,12,[57][58][59][60][61][62][63][64] A few years ago, two independent groups showed that loss-of-function mutations in the human TRPM6 gene are the molecular cause of HSH. 10,56 HSH is an autosomal recessive disease that manifests in early infancy with generalized convulsions or symptoms of increased neuromuscular excitability including muscle spasms and tet-any.…”
Section: Role Of Trpm6 Channels In Renal Magnesium Homeostasismentioning
confidence: 99%
“…Mechanical stress such as membrane stretch or osmotic cell swelling can activate TRPM7--like channels (Numata et al, 2007), which are involved in Mg transport. These channels are members of the ubiquitously expressed melastatin--related subfamily of transient receptor potential (TRP) channels, and represent essential mediators of anoxic neuronal death Penner and Fleig, 2007). Low intracellular levels of Mg, a process that exacerbates the effects of stress on the organism, also activate TRPM7 channels.…”
Section: Neurological Function Of Magnesiummentioning
confidence: 99%